TerasDigital: Community-based digital education innovation as a strategy to improve generation z’s competence to reduce unemployment in the digital economy era - Intan Eka Amelia; Latifah Mufid Rinayanti; Septi Yulisetiani (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The rapid development of the digital economy has created new challenges, including the rising unemployment rate among Generation Z due to a lack of competencies aligned with industry needs. The gap between young graduates’ skills and the demands of the job market has become a key factor contributing to this issue. This study aims to provide a solution through TerasDigital, a community-based platform promoting digital education. Previous studies highlight that community learning and digital literacy play essential roles in enhancing employability among young generations. Methods: This study employs a literature review and digital labor trend analysis to identify the competency gap among Generation Z. Secondary data from national and global employment reports were analyzed to design programs aligned with the needs of the digital industry, focusing on critical thinking, public speaking, collaboration, creativity, project management, and technological proficiency. Findings: Analysis shows that addressing the competency gap among Generation Z requires an integrated ecosystem that goes beyond technical training by incorporating adaptive soft skills, professional guidance, and project-based collaboration. TerasDigital functions conceptually as a strategic bridge to narrow this gap, transforming non-formal education into a center for skills development and professional networking that is aligned with the needs of the digital industry. This model emphasizes that reducing digital unemployment depends on creating an accessible, community-driven environment that facilitates peer interaction and real-world project experience. Conclusion: TerasDigital is expected to serve as an effective and sustainable strategy to address competency disparities, enhance Generation Z’s competitiveness, and reduce unemployment amid the massive digital transformation. Novelty/Originality of this article: This study introduces TerasDigital as an innovative community-based digital education model that combines digital literacy, professional mentoring, and project-based learning to directly align Generation Z’s skills with the evolving needs of the digital economy.